Formigas associadas a Turnera subulata (Turneraceae) : custos e/ou benefícios para planta hospedeira? - Cruz, Nayara Gomes da (2016)
Ecological interactions between organisms are complex and can present dynamic results, which are dependent on environmental context. Plants with extrafloral nectaries attract a wide variety of ants species, in associations commonly considered mutualistic. In tropical environments the combination of plants and ants play an important role in communities. Turnera subulata is a ruderal shrub widely distributed in disturbed areas, which has a pair of extrafloral nectaries in the base of each leaf. In this study, we evaluated whether the ants associated with T. subulata: (i) vary spatially (between locals) and temporally (over day period); (ii) respond to simulate presence of herbivores and the signs of damage caused in different structures of the host plant (stem and leaf); (iii) reduce herbivory rates; (iv) influencing the vegetative growth and reproductive success of the host plant, along its phenology. The experiments were conducted in São Cristóvão-SE. For the initial understanding of the system studied, T. subulata individuals were selected, in which we performed simulations of the presence of herbivorous and realization of injuries in the stem and leaves of the host plants. The total number of individuals and species associated ants was quantified during three periods of the day. It was quantitated the percentage of leaf area lost and leaves attacked by sucking. They also plot experiments were performed in which were established with and without ants. In each plot were transplanted T. subulata seedlings that were followed throughout their phenological stages. Observations were made in order to quantify the vegetative growth and reproductive investment measures the host plant as well as the number of sheets to damage by sucking insects and chewing; and the number of herbivores. The number of visitors associated with T. subulata was quantified during three periods of the day, being held 5min observation / share. In all cases, data were analyzed using general linear models. 21 species of ants were found. The composition of the ant meeting showed significant variation between locations and time of day. Visitation rates and predation by ants was higher in stems than in the leaves of plants. In general, herbivory rates were not correlated with the association / activity of ants, with the exception of leaf area proportion consumed, which showed a significant reduction in plants where the ants defended the leaves. The results showed that the maturation stage there was a trade-off between growth x propagation of plants; which is favorable for plants (ex.: higher reproduction) who were in plots with ants. Plants on treatment with ants had fewer visitors, including predators and parasitoids. The number of sucking herbivores was significantly reduced in the presence of ants, during the flowering stage. Our results suggest that the benefits of the association may be dependent on context. Moreover, they can contribute to the understanding of the mechanisms involved in facultative interactions between ants and plants and to the understanding of the communities in interaction nets.